Workplace harassment & discrimination faced by women at District Dera Ghazi Khan - Aisha Khan; Uzma Masroor (International Journal on Women Empowerment, 2019)
Background: Gender based workplace harassment has existed in one form or another ever since men and women began interacting at educational institutes or workplaces. Pakistani women are facing great difficulty in their workplace due to harassment and discrimination they face in their daily life. The aim of this study was to identify the causes and reasons of harassment among working women at Dera Ghazi Khan. Methodology: This cross-sectional study continued for one year from 2010 to 2011, including women working at various public and private institutions of Dera Ghazi Khan (DGK). A total of 180 working women were selected through convenience sampling. Data including sociodemographic characteristics together with harassment history like type of harassment experienced, knowledge and perceptions regarding harassment was recorded through a pre-designed questionnaire. The collected data was then analyzed using SPSS Version 17.0. Results: Based on the study results women mostly faced discrimination regarding education (23%), disability (11%), job status (8%), marital status (5%), appearance (7%) and gender-related (9%), etc. Around 98% women reported that they had experienced workplace harassment and the mode of harassment was mostly verbal i.e. 96%. Moreover, 82% women reported that the disclosure of the harassment event was not encouraged at their workplace, one of the major reasons for this was thought be the pressure from the management. Out of the total only 13.3% women were having knowledge of harassment bill passed in 2010. Loneliness, isolation and loss of interest in outings were few of the effects caused in response to workplace harassment. Conclusion: It is evident that the workplace harassment incidences are frequent in DGK but due to societal pressures, majority remain unreported. It is recommended that females must know their rights and government must take suitable measures to build up strong anti- harassment policies in order to strengthen women in this regard.